1998
DOI: 10.1016/s1074-5521(98)90157-0
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a minimal modular polyketide synthase, and targeted alteration of the stereospecificity of polyketide chain extension

Abstract: These results demonstrate that, as predicted, even a single-module PKS is catalytically active in the absence of other DEBS proteins. In its normal context, the ketosynthase domain KS1 is thought to generate a (2S)-2methyl-3-hydroxy intermediate by epimerising the initial product of carbon-carbon chain formation, the (2R)-2-methyl-3-ketoester. The observed formation of the alternative (2R)-methyl-3-hydroxy product catalysed by DKS1-2 provides strong support for this proposal, and indicates how targeted alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…[30] In the present case, bringing KR 5 into a chimaeric module with KS 2 did not lead to any loss of stereospecificity or stereoselectivity; this supports a model for catalysis [26,27,30] in which DEBS KS 2 differs from KS 1 in that it cannot catalyse the epimerisation of the (2R)-2-methyl-3-ketopentanoyl-ACP intermediate, or cannot do so fast enough to compete with ketoreduction. This experiment also shows that the ACP-tethered diketide is reduced with full fidelity by KR 5 , even though previous in vitro studies have shown that recombinant purified KR 5 reduces the (untethered) racemic substrate (2RS)-2-methyl-3-oxopentanoic acid N-acetylcysteamine thioester to give three stereoisomeric products.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…[30] In the present case, bringing KR 5 into a chimaeric module with KS 2 did not lead to any loss of stereospecificity or stereoselectivity; this supports a model for catalysis [26,27,30] in which DEBS KS 2 differs from KS 1 in that it cannot catalyse the epimerisation of the (2R)-2-methyl-3-ketopentanoyl-ACP intermediate, or cannot do so fast enough to compete with ketoreduction. This experiment also shows that the ACP-tethered diketide is reduced with full fidelity by KR 5 , even though previous in vitro studies have shown that recombinant purified KR 5 reduces the (untethered) racemic substrate (2RS)-2-methyl-3-oxopentanoic acid N-acetylcysteamine thioester to give three stereoisomeric products.…”
supporting
confidence: 80%
“…Lactones 4 a and 5 a are the hypothetical products from hybrid DEBS1-TE containing either DEBS KR 1 or RIFS KR 7 in the reductive loop of module 2 based on the activity of these reductive enzymes in their native context, but are not expected to form owing to the absence of catalysed epimerisation activity in DEBS module 2. [26,27,42] has shown the importance from a synthetic viewpoint of trying more than one example of a desired hybrid. The results found here illustrate clearly that a different choice of splice sites, and/or use of a different donor reductive loop, can very significantly affect the yield of the desired novel polyketide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Since each of these modules is known to act completely stereospecifically when processing both natural and unnatural enzyme-bound substrates, 5,22b it is likely that the loss of stereochemical control in reduction of the ketodiketide-SNAC analog 13 may reflect the requirement that the substrate be covalently anchored to the ACP domain for proper positioning and orientation in the KR active site. Indeed, the results reported here confirm that recombinant DEBS KR2 and KR6 both catalyze completely stereospecific reductions of ACPbound 2-methyl-3-ketotriketides that have been generated in situ by the action of a 32 No conclusions could be drawn as to whether KR2 exercises any selection against the diastereomeric L-2-methyl-3-ketopentanoyl-ACP, which may or may not have been transiently formed by the hybrid DKS1-2 enzyme.…”
Section: Analysis Of Kr Stereospecificitymentioning
confidence: 63%
“…1B). Progress has recently been made in this direction by studying the 6-deoxyerythronolide B synthase in vivo or in vitro, leading to the finding that the stereochemistry of the alkyl-branched center or the oxygenated center is controlled by the ketoacyl synthase (KS) (10,31,52) or the ketoreductase (KR) (10,25), respectively, in the specific cases examined. However, these studies fall short of providing a satisfactory explanation at the molecular level of how a given KS or KR exhibits its stereospecificity; sequence comparison among various KS or KR domains has also failed to reveal any conserved motifs that could potentially be ascribed to their opposite stereospecificities.…”
Section: Discussionmentioning
confidence: 99%